Evaluation of the thermo-hydraulic behavior of water-based graphene and Al2O3 hybrid nanofluids in a circular tube through CFD simulations - Oflaz, Fatma (Springer, 2025)
This study presents an in-depth computational investigation of the thermohydraulic performance of water-based hybrid nanofluids containing graphene and aluminum oxide (Al2O3) nanoparticles. Using computational fluid dynamics (CFD) software, the research focused on understanding the behavior of these nanofluids under turbulent flow conditions in a circular tube. The analysis included examining how various parameters, including the Nusselt number, friction factor, and performance evaluation criteria, were influenced by the addition of nanoparticles. Five different nanoparticle volume concentrations, ranging from 0.1 to 1%, were analyzed. The simulation was conducted for turbulent flow regimes using Reynolds numbers between 20,000 and 80,000. A constant surface heat flux boundary condition was applied to the tube. The k-epsilon RNG (Renormalization Group) turbulence model was used as it is suitable for capturing turbulence effects in such flows. The thermophysical properties of the hybrid nanofluids were calculated using correlations available in the literature. The addition of graphene and Al2O3 nanoparticles significantly increased the Nusselt number, demonstrating enhanced heat transfer performance. The improvement in the Nusselt number was observed across all volume concentrations and Reynolds numbers. The maximum enhancement (28%) was recorded compared to pure water at 1% volume concentration. The friction factor increased with the addition of nanoparticles due to the higher viscosity of the hybrid nanofluids. The highest increase in the friction factor was 7.2% at the maximum volume concentration of 1%. The increase in viscosity contributed to an increased pressure drop in the system. However, the magnitude of this increase was relatively modest compared to the heat transfer benefits. The PEC (Performance Evaluation Criteria) value was found to be greater than 1 in most cases. The highest PEC value of 1.26 was achieved at the lowest Reynolds number (20,000) and the highest nanoparticle concentration (1%). This indicates that the use of the hybrid nanofluid is thermohydraulically advantageous under these conditions. The study concludes that water-based hybrid nanofluids containing graphene and Al2O3 nanoparticles enhance heat transfer performance significantly, making them suitable for applications requiring efficient thermal management. The slight increase in flow resistance was outweighed by the substantial heat transfer improvements, particularly at higher volume concentrations and lower Reynolds numbers, as reflected by the favorable PEC values.
Keywords: Hybrid nanofuids; Heat transfer enhancement; Thermal and hydraulic performance; CFD